2016
DOI: 10.3855/jidc.7324
|View full text |Cite
|
Sign up to set email alerts
|

Glycated hemoglobin screening identifies patients admitted for retreatment of tuberculosis at risk for diabetes in Tanzania

Abstract: Introduction World Health Organization recommendations of bidirectional screening for tuberculosis (TB) and diabetes have been met with varying levels of uptake by national TB programs in resource-limited settings. Methodology Kibong’oto Infectious Diseases Hospital (KIDH) is a referral hospital for TB from northern Tanzania, and the national referral hospital for multidrug-resistant (MDR)-TB. Glycated hemoglobin (HgbA1c) testing was done on patients admitted to KIDH for newly diagnosed TB, retreatment TB, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“… 12 13 Likewise, the incidence of dual diagnosed patients with TB/DM ranges from 4% of all patients with TB in rural areas to 17% in urban settings. 14 15 Evidence has shown that TB/DM death is fivefold higher compared with patients with TB without DM and that death primarily occurred early, in the first 3 months of TB treatment. 14 15 This high and early mortality from TB/DM in Tanzania is due to both programmatic and biological factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 13 Likewise, the incidence of dual diagnosed patients with TB/DM ranges from 4% of all patients with TB in rural areas to 17% in urban settings. 14 15 Evidence has shown that TB/DM death is fivefold higher compared with patients with TB without DM and that death primarily occurred early, in the first 3 months of TB treatment. 14 15 This high and early mortality from TB/DM in Tanzania is due to both programmatic and biological factors.…”
Section: Introductionmentioning
confidence: 99%
“… 14 15 Evidence has shown that TB/DM death is fivefold higher compared with patients with TB without DM and that death primarily occurred early, in the first 3 months of TB treatment. 14 15 This high and early mortality from TB/DM in Tanzania is due to both programmatic and biological factors. 16 The TB and DM services are not linked and these separated service lines lead to delayed interventions for both diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The WHO recommend bidirectional screening of DM and TB [20], however, this has been implemented to varying degrees in LMICs such as Tanzania [6]. Bidirectional screening for TB and DM is reported to give high yield for TB among DM patients and vice versa [21–23].…”
Section: Introductionmentioning
confidence: 99%
“…The authors consider body mass index, as it shows an inverse correlation to the rifampicin concentration in the body [ 46 ]. Another point is the authors did not focus on the DM status but the latest Hba1c point [ 47 ]. This is important as some of the DM patients may have controlled HbA1c which possibly reduces the occurrence of DR-TB.…”
Section: Discussionmentioning
confidence: 99%